2011
DOI: 10.1080/10937404.2011.578557
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Endocrine Disruptors: Possible Involvement in Brain Development and Neurodegeneration

Abstract: Environmental chemicals that act as endocrine disruptors do not appear to pose a risk to human reproduction; however, their effects on the central nervous systems are less well understood. Animal studies suggested that maternal exposure to endocrine-disrupting chemicals (EDC) produced changes in rearing behavior, locomotion, anxiety, and learning/memory in offspring, as well as neuronal abnormalities. Some investigations suggested that EDC exert effects on central monoaminergic neurons, especially dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 168 publications
(158 reference statements)
2
75
0
4
Order By: Relevance
“…Although an emerging body of evidence suggests that an endocrine disruptor such as bisphenol A exerts its effects on the central nervous system (CNS) in rodents (Masuo and Ishido, 2011), there is little information about the effects of p-nitrotoluene on the CNS. Previously, we demonstrated that intracisternal administration of p-nitrotoluene causes hyperactivity in the Wistar male rat (Ishido et al, 2004), following the protocol by Shaywitz et al (1976).…”
Section: Introductionmentioning
confidence: 99%
“…Although an emerging body of evidence suggests that an endocrine disruptor such as bisphenol A exerts its effects on the central nervous system (CNS) in rodents (Masuo and Ishido, 2011), there is little information about the effects of p-nitrotoluene on the CNS. Previously, we demonstrated that intracisternal administration of p-nitrotoluene causes hyperactivity in the Wistar male rat (Ishido et al, 2004), following the protocol by Shaywitz et al (1976).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that in utero and early postnatal exposure to BPA produce a broad range of adverse effects (10)(11)(12). Historically, endocrine-reproductive and immune function-related abnormalities were documented first, and impaired brain development and behavior have been linked to BPA exposure more recently (13)(14)(15).…”
mentioning
confidence: 99%
“…Değişen bu fizyolojik durum kendini bilişsel fonksiyonda gerileme, stres yanı-tında değişim, sosyoseksüel ve ebeveyn davranışla-rında bozulmalar şeklinde gösterebilmektedir. 15,16 Nöroendokrin bozucu kimyasal maddelere bağlı etkiler ve bu konuda yürütülen hayvan çalışmaları farklı başlıklar altında aşağıda sunulmuştur.…”
Section: Nöroendokri̇n Bozucu Ki̇myasal Maddeler İle Yürütülen Hayvan çunclassified
“…Turkiye Klinikleri J Neur 2018;13(1): [7][8][9][10][11][12][13][14][15][16][17][18][19] lar, DEHP maruziyetine erkek ve dişilerin yaş ve doz-yanıt eğrisi açısından farklı yanıtlar verdiğini göstermektedir. 19 Hipotalamustaki anteroventral periventrikü-ler çekirdek (AVPV) ve cinsel dimorfik çekirdek-mediyal preoptik alan [sexually dimorphic nucleus of the preoptic area (SDN-POA)] cinsiyete özgü üreme fizyolojisi ve davranışlarda rol oynamakta ve her iki bölge de östradiole bağlı olarak cinsiyete bağlı gelişim göstermektedir.…”
Section: Ci̇nsi̇yete Bağli Etki̇lerunclassified